2020
DOI: 10.1136/bmjopen-2019-033211
|View full text |Cite|
|
Sign up to set email alerts
|

Reliability and validity of the Chinese version of the Patient Health Questionnaire-9 (C-PHQ-9) in patients with psoriasis: a cross-sectional study

Abstract: ObjectiveTo evaluate the clinical reliability and validity of the Chinese version of the Patient Health Questionnaire-9 (C-PHQ-9) in patients with psoriasis.DesignCross-sectional study.SettingTertiary care centre.ParticipantsPatients with psoriasis who have not been diagnosed with depression (n=148; mean age 43.37±17.46 years; 31.19% female).Primary and secondary outcome measuresThe primary outcome measures considered in this study were the C-PHQ-9 and the Hamilton Depression Scale (HAMD). The American Diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 20 publications
2
23
0
Order By: Relevance
“…After exclusion of incomplete questionnaires, 326 (response rate 71%) were qualified for further analysis, including 159 patients with psoriasis (108 males and 51 females) and 167 non-psoriatic controls (84 males and 83 females). The two groups were agematched, and the differences in sex ratio (27) and BMI (28) were consistent with previous epidemiological findings. The summary of demographic and clinical details was described in Table 1.…”
Section: Higher Incidence Of Gastrointestinal Discomfort Symptoms In Patients With Psoriasis Than Common Populationsupporting
confidence: 87%
“…After exclusion of incomplete questionnaires, 326 (response rate 71%) were qualified for further analysis, including 159 patients with psoriasis (108 males and 51 females) and 167 non-psoriatic controls (84 males and 83 females). The two groups were agematched, and the differences in sex ratio (27) and BMI (28) were consistent with previous epidemiological findings. The summary of demographic and clinical details was described in Table 1.…”
Section: Higher Incidence Of Gastrointestinal Discomfort Symptoms In Patients With Psoriasis Than Common Populationsupporting
confidence: 87%
“…A recent meta-analysis showed that the sensitivity of the PHQ-9 was lower (0.77 versus 0.88) when using the MINI as the gold standard compared to semi-structured interviews [ 40 ]. In the present study, there was a strong correlation between the total scores of HAMD-17 and PHQ-9, which was consistent with previous findings [ 41 , 42 ]. These findings support the validity and feasibility of the use of PHQ-9 for assessing depression severity.…”
Section: Discussionsupporting
confidence: 93%
“…The total score of the scale is 27 points, higher than 5 points indicate mild depression, higher than 10 points indicate moderate depression, and higher than 15 points indicate severe depression. The Chinese version of PHQ-9 has been validated in previous studies (α = 0.94) [19].…”
Section: Psychosomatics Factorsmentioning
confidence: 99%